Analysis of Patient Characteristics on Potential Drug Interactions in Intensive Care Unit (ICU) Patients at Dr. R Soedjati Purwodadi Grobogan Hospital - Eko Retnowati Nabilla; Malika Audrey; Intan Adevia Rosnarita (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to analyze patient characteristics associated with potential drug interactions among Intensive Care Unit (ICU) patients at Dr. R Soedjati Purwodadi Grobogan Hospital. It was hypothesized that patient-related factors, particularly the number of prescribed drugs, would influence the occurrence of potential drug interactions. Research Method: This quantitative observational study employed a retrospective cross-sectional design using ICU medical records from January to October 2025. Drug interaction screening was conducted using Medscape and Drug Interaction Checker. The variables included age, sex, comorbidities, number of drugs, interaction severity, and interaction mechanism. Data were analyzed using univariate and bivariate analysis. Results and Discussion: A total of 255 potential drug interactions were identified, with most classified as moderate (56.9%) and pharmacodynamic (62.7%). Most patients were elderly, female, and had comorbidities. Statistical analysis showed no significant relationship between age, sex, or disease history and potential drug interactions, whereas the number of drugs prescribed was significantly associated with interaction occurrence (p < 0.001). Implications: These findings emphasize that polypharmacy is the main determinant of potential drug interactions in ICU patients. Strengthened clinical monitoring, prescription review, and pharmacist involvement are needed to improve medication safety in intensive care settings.